Examination for employee’s satisfaction to develop the organisational culture - Szilágyi, Barnabás (Acta Agraria Debreceniensis, 2006)
This examination for employee’s satisfaction analyzes relationships which influence the general feelings of workers and which are revealing in horizontal and vertical. On the whole we can observe that the workers find their horizontal relationships good. In the co-worker’s relationship the appreciation and the confidence appear. Inside departments and between departments the good relationship is typical which is indispensable for the effective work. It is interesting that more than 40% of employees find their chief as „ideal superior”. The quality of vertical relation is determined by human relationships. This result is interesting because the management style is not participative in this organisation.